Peningkatan Daya Saing Usaha Ayam Penyet Budhe Sutet Melalui Strategi Promosi - Adinda Adinda; Jonathan Owen M; Kent Valentino; Louis Halim; Lydia Setiawan; Nadya Putri Anjani; Stephanie Shiela C.S.; Santi Rimadias (Lembaga Pengembangan Kinerja Dosen, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have an important role in driving Indonesia's national economy, where the culinary sector is located. Ayam Penyet Budhe Sutet, a culinary MSME, faces a major challenge in its promotional strategy, limiting its visibility and customer reach. To overcome this, community service programs are implemented to increase competitiveness through a series of targeted initiatives, including redesigning banners, updating menu lists, creating promotional materials for social media, and registering business locations on Google Maps. These efforts aim to increase brand exposure, simplify operational processes, and attract more customers. The expected results include increased sales, increased market presence, and increased business sustainability, thereby contributing to the growth of Indonesia's culinary MSME sector